EFFECTS OF GLYCYRRHIZIN PRE-TREATMENT ON TRANSIENT ISCHEMIC BRAIN INJURY IN MICE - Lim, Chiyeon; Lim, Sehyun; Lee, Young-Jun; Kong, Bokcheul; Lee, Byoungho; Kim, Chang- Hyun; Kim, Buyeo; Cho, Suin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Ischemia-induced brain damage is the leading cause of adult disability and the fifth leadingcause of death, and thus, the development of anti-apoptotic neuro-protective therapeutic agents is viewed asan attractive developmental strategy. Glycyrrhizin is the main sweet component in licorice and has a numberof pharmacological activities, which include neuro-protective, anti-fungal, and anti-cariogenic activities.This study was undertaken to investigate the effects of glycyrrhizin on ischemia-induced brain damage.Materials and Methods: In infarct volumes and the levels of several apoptosis-related proteins, caspase-3, -8, 9, Bcl-xL, Bcl-2,and their activities in the brains of middle cerebral artery occlusion (MCAO) treated micewere measured using western blotting methods.Results: Single pre-treatment with glycyrrhizin (10-100 mg/kg)at 2 hours before MCAO significantlyreduced infarct volumes at 24h after MCAO. In addition, glycyrrhizin effectively inhibited the activations ofcaspase-3 and -9 and the down-regulation of Bcl-xLprotein caused by MCAO.Conclusion: The neuro-protective effect of glycyrrhizin was found to be due to its regulation of apoptosisrelatedproteins signals.The authors suggest glycyrrhizin be considered a potential candidate for thetreatment of ischemia induced brain damage.